La mediación en la solución de conflictos y la simplificación de los trámites en los procesos de naturaleza transigible - Ferrin Zambrano, Asunción del Consuelo (2014)
This thesis, whose theme is about "Mediation in Conflict Resolution and Simplification of formalities in Nature Transigible Processes" has been developed in response to the need to expand the service coverage of justice administration in the country, where the mediation plays an important role. In the chapter I, it´s talk about the problem that Ecuadorian justice is coming, about stopping those cases in the court, and the little diffusion as solutions to these problems by the mediation. In the chapter II, at the theory mark in Equator, the possibility to come up to alternatives methods, it’s too far to get preferences of the parts, because there is a new litigious´ culture, that before to search a pacific solution, they go to the judicial litigious. In the chapter II, through methodologist it had been applying all methods: inductive, deductive, analytic synthetics, scientific and comparative. In the chapter IV, it had made interviews to the judges, lawyers in free professional practice and it had made requests to the rights´ students of fifth year of Quevedo´s University. In the chapter V, we find out to the conclusion that the bibliographic and documental investigation, get it determiner the normative, doctrinarian and judicial field of the mediation as a way to easy access to the conflicts solutions and the recommendations that will ought be considered the mediation as obligatory, previous to substantiation of cases by judicial way. In the chapter VI, in the proposal, it establish the reform the Art 52 of the arbitrage and mediation´s law where the judicature council should organizer more mediation centers